Heteropolyacid supported on acidic clay: a novel efficient catalyst for alkylation of ethylbenzene with dilute ethanol to diethylbenzene in presence of C-8 aromatics - Bokade, Vijay V.; Yadav, Ganapati D. (Journal of Molecular Catalysis A-Chemical, 2008)
Vapor phase alkylation of ethylbenzene with ethanol to diethylbenzene is industrially relevant. Diethylbenzene is an important raw material for the conversion of divinyl benzene monomer. Conventionally, it is prepared from diacetophenone by reduction. It is also prepared by vapor phase alkylation of ethylbenzene with ethylene using zeolitic catalysts. The efficacy of dodecatungsotphosphoric acid (DTPA) supported on acid treated clay has been evaluated in the current work in the alkylation of ethylbenzene with 80% (w/w) ethanol. 15% (w/w) DTPA/K-10 clay was found to be an efficient and robust catalyst. The use of aqueous ethanol and a mixed C-8 stream lowers the cost of production. A kinetic model is developed by studying the important process parameters with 15% (w/w) DTPA/K-10 as the catalyst. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Alkylation; diethylbenzene; Heteropolyacid; kinetics; Solid acids

Festschrift in Honor of Dr. B. D. Kulkarni - Yadav, Ganapati D.; Jayaraman, Valadi K.; Ravikumar, V. (Industrial & Engineering Chemistry Research, 2009)

Transesterification of edible and nonedible vegetable oils with alcohols over heteropolyacids supported on acid-treated clay - Bokade, Vijay V.; Yadav, Ganapati D. (Industrial & Engineering Chemistry Research, 2009)
In the current work, the novelty of heteropolyacid on clay (K-10) for the transesterification of vegetable oil with lower and higher alcohols is presented. Methyl esters (biodiesel) and glycerol were produced by the transesterification of vegetable oil with methanol in the presence of dodecatungestophosphoric acid (DTPA) supported on K-10 clay. The transesterification consists of three consecutive reversible reactions Diglycerides (DG) and monoglycerides (MG) are intermediate products. The optimal catalyst concentration was 5% w/w of oil. Detailed studies were done for optimization of the process parameters. The rate of transesterification in a batch reactor increased with temperature up to 170 degrees C. Higher temperatures did not reduce the time to reach maximum conversion. The study was also extended to reactions of different edible and nonedible oils with lower and higher alcohols. The conversion of TG, DG, and MG seemed to be a second-order mechanism for the forward and reverse reactions, where the reaction system could be described as a pseudo-heterogeneous catalyzed reaction. The reaction rate constants for the TG. DG, and MG transesterification reactions were 0.12-0.84 h(-1) and were higher for the MG reaction than for the TG transesterification. The activation energies were 4.2, 26, and 7.4 kcal/mol for the TG, DG, and MG transesterification reactions, respectively. The proposed kinetic model fits the experimental results well.

Heteropolyacid supported on montmorillonite catalyst for dehydration of dilute bio-ethanol - Bokade, Vijay V.; Yadav, Ganapati D. (Applied Clay Science, 2011)
Vapour phase dehydration of dilute bio-ethanol (EtOH) to ethylene (E) and diethyl ether (DEE) is industrially relevant. Ethylene is an important raw material for many petrochemical products and Diethyl ether (DEE) can be used as an alternative fuel. The efficacy of montmorillonite (K-10) and dodecatungestophosphoric acid (DTPA) supported on montmorillonite (DTPA/K-10), has been evaluated in the current work in the dehydration of dilute bio-ethanol (80%m/m). The dehydration of ethanol and cracking of diethyl ether were studied independently. 30% m/m DTPA/K-10 was found to be more active with 74% ethanol conversion and 92% ethylene selectivity at 250 degrees C in comparison with other acid catalysts used. The merit of the process lies in its use of dilute bio-ethanol, a new avenue for ethylene production from a non-petroleum feedstock. Kinetic interpretation has been made by studying the important process parameters by using 30%m/m DTPA/montmorillonite as the catalyst. The mechanism of the dehydration of ethanol reaction suggests that two types of sites are responsible. The dehydration of ethanol and cracking of diethyl ether are second order reactions with weak adsorption of species. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bio-ethanol; dehydration; Diethyl ether; Ethylene; Heteropolyacid

Dodecatungstophosphoric acid supported on acidic clay catalyst for disproportionation of ethylbenzene in the presence of C-8 aromatics - Bokade, Vijay V.; Yadav, Ganapati D. (Industrial & Engineering Chemistry Research, 2012)
Vapor-phase disproportionation of ethylbenzene (EB) to diethylbenzene (DEB) in a single step is industrially relevant. Diethylbenzene is an important raw material for the conversion of divinylbenzene monomer. Conventionally, it is prepared from diacetophenone by reduction. It is also prepared by vapor-phase alkylation of ethylbenzene with ethylene/ethanol using zeolitic catalysts. In the current work, the efficacy of dodecatungstophosphoric acid (DTPA) supported on acid-treated clay has been evaluated in the disproportionation of ethylbenzene. A 20% (w/w) DTPA/K-10 clay catalyst was found to be efficient and robust. An industrial feed having different compositions of ethylbenzene and xylene isomers was used for the experimentation. Hence, they were expected to hinder the movement of reactant molecules on the catalyst surface. It was observed that irrespective of feed composition the concentration of the xylene isomers was intact in the product. There was no other byproduct formation like p-ethylrnethylbenzene. Optimization of process parameters is presented. The effect of varying the concentration of aromatic compounds in the feed on ethylbenzene conversion and product distribution over the plain clay (K-10) and heteropolyacid-loaded clay catalyst have been discussed. The effect of catalyst bed length to inner diameter of reactor (L/D) ratio on the ethylbenzene conversion and selective formation of p-diethylbenzene (p-DEB) are also discussed.